Reducing process time of PV module lamination by using double-side heating system - Sraisth; Mansour Djamel Eddine; Öz Aksel Kaan; Gebhardt Paul; Klaus Daniel; Wellens Christine (EPJ Photovoltaics)
Non-optimized encapsulation parameters, set during the lamination process, can be a cause of multiple failure modes for PV modules in the field. This paper investigates the influence of a double-side heating system in the lamination process for a glass-backsheet PV module. This effect was evaluated by comparing the gel content of encapsulants treated with different heating methods, including single-side and double-side heating systems. Towards this goal, forty different lamination process recipes are tested using various temperatures and process times to compare the gel content of the ethylene vinyl acetate (EVA) encapsulant and find the fastest possible lamination process. The gel content is determined using Soxhlet extraction, while the degree of crosslinking is assessed using differential scanning calorimetry (DSC), and the results are compared. The results show that double-side heating can shorten the process time by 10% to 30%. Furthermore, the paper examines the potential of reducing the process time by performing temperature uniformity measurements during the process and laminating full-size modules for visual inspection using a double-side heating system. It was found that temperatures above 165 °C can be used for a stable lamination process using EVA encapsulant and polyethylene terephthalate (PET) based polymer backsheet. Based on the above results, a five-minute one-step single-press lamination process plus cooling is demonstrated. Long-term stability and safety tests are further studied according to IEC 61215-2 and IEC 61730-2 standards, respectively. The modules successfully passed the standard qualification tests, including thermal cycling, damp-heat, and mechanical load tests following damp-heat exposure, with a maximum power degradation (PMPP) of less than 2%. All the insulation characterizations, including the dry insulation test and wet leakage current test, were also successfully completed following the safety tests, which included sequence B and sequence B1.